Desarrollo del área del lenguaje en niños y niñas de educación inicial ll - Carvajal Armendáriz, Liliana Elizabeth (2017)
The present research is focused on analyzing the principal language problems that can exist in the children of nursery education II. The type of methodology used was quantitative qualitative, the population was placed 25 students, 25 parents and 2 teachers. As collection instrument data, researchers used the checklist, through observation, to better understand the children development in the classroom also interview and the questions, were done to teachers, the survey and the questionnaire to the parents and surveys was tabulated in order to understand better the research problem, also bibliographical sources on the research were investigated to obtain the theoretical framework….